How Entrepreneurship Education and Social Support Affect Students’ Entrepreneurial Intentions in Jakarta Vocational Schools: Moderation by Self-Efficacy - Larasati Indah Lestari; Dr. Rd. Tuty Sariwulan, M.Si; Dr. Siti Nurjanah, SE., M.Si (Journal of Digital Business and Global Economy, 2025)
This study aims to analyze the influence of Entrepreneurship Education and Social Support on Entrepreneurial Intention, moderated by Self-Efficacy, among students of SMK Negeri 44 Jakarta, SMK Negeri 14 Jakarta, and SMK Negeri 31 Jakarta. The research employs a quantitative approach with data analysis using the Structural Equation Modeling (SEM) method via the SmartPLS application, involving 187 student respondents. The results show that Entrepreneurship Education has a positive and significant effect on Entrepreneurial Intention (H1), and Social Support also positively influences Entrepreneurial Intention (H2). Self-Efficacy is proven to positively moderate the relationship between Entrepreneurship Education and Entrepreneurial Intention (H3). Conversely, Self-Efficacy negatively moderates the relationship between Social Support and Entrepreneurial Intention (H4).